WASATHIYYAH PERSPEKTIF MISBAH MUSTOFA: (Studi Tafsir Al-Iklīl Fī Ma‘anī Al-Tanzīl) - Maulida, Fahma; Anindita, Amalia (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Wasathiyyah is an Islamic teaching that directs its followers to be fair, balanced and proportional, or known as moderation in all aspects of life. The principles of Wasathiyyah in Islam are an important discourse to study, so that they become a true foundation in understanding the concept of Wasathiyyah. This study aims to further explore the Wasathiyyah principles from the perspective of Misbah Mustofa in the interpretation of Al-Iklīl Fī Ma'ānī Al-Tanzīl. This research is a type of library research and uses a descriptive-analytical method in analyzing the findings of the data. The conclusion obtained from the results of this study is that there are three principles of wasathiyyah in Islam. First, al-Wasat in QS. al-Baqarah [2]: 143; Second, al-Wazn in QS. al-Hadid [57]: 25. Third, al-'Adl in QS. al-A'raf [7]: 181. According to Misbah Mustofa these three principles have the same meaning, namely to behave and act fairly to all human beings without discriminating against race, class and religion. Keywords: Wasathiyyah, Misbah Mustofa, Al-Iklīl Fī Ma‘ānī Al-Tanzīl